Analisis Titik Pulang Pokok Usaha Kerajinan Tangan Kayu Hitam (Ebony) Pada UD. Krisna Karya Ebony Di Kota Palu - Lawidu, Lani MA. (AGROTEKBIS, 2013)
Ebony attempt at UD. Ebony krisna work is industrial enterprises that produce handicrafts that are in the district of East Palu Palu. UD. Ebony krisna work has 2 types namely superior product ebony clock key chains and wall anchors. This study aims to analyze the break-even point for the production of key chain and anchor wall clock, knowing the magnitude of the physical production, the cost of production, selling price and the amount of revenue that the UD. Ebony Krisna work. The research was conducted at UD. Primary data obtained by direct observation and interviews with the respondents, led UD. Ebony Krisna work, while the secondary data obtained from the relevant agencies and the relevant literature for the purpose of this study. The results showed that the break-even point is achieved keychains products at production volumes of 2,261 pieces with a price of Rp 4.500/buah, the total cost is equal to total revenue of Rp 10,174,500. Even point anchor wall clock products of 100 pieces with a price of Rp 175.000/buah, the total cost is equal to total revenue of Rp 17,500,000.